PLANNING AND PREDICTING AS SYSTEM ELEMENTS OF GROUNDING THE PROSPECTIVE DEVELOPMENT OF EDUCATIONAL ESTABLISHMENTS - A. Kurakov (Russian Journal of Economics and Law)
The article presents the theoretical approach to grounding the results of prospective development of professional educational establishments by interaction between planning and predicting in the management system.